Preparation process of quick-drying vinylidene chloride paint layer
The use of a modified nano-silicon dioxide and expanded perlite filler, combined with ultrasonic spraying, enhances the adhesion and drying speed of perchloroethylene paint layers, improving durability and addressing slow-drying issues.
Patent Information
- Application Number
- CN202411730477.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-11-29
AI Technical Summary
Perchloroethylene paint layers used in heat shields dry slowly, leading to poor adhesion, peeling, and performance degradation, affecting the service life and safety of the product.
A preparation process involving the use of a filler composed of modified nano-silicon dioxide and expanded perlite, combined with an ultrasonic spraying method, to enhance adhesion and drying speed, including steps of dispersing and ball-milling these components with specific additives and solvents, followed by ultrasonic application on a substrate.
The process results in a quick-drying perchloroethylene paint layer with improved adhesion and durability, addressing the slow-drying issues of traditional methods.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of perchloroethylene paint layer preparation, and relates to a preparation process of a quick-drying perchloroethylene paint layer. Background Art
[0002] Perchloroethylene paint has many advantages, such as quick drying, good atmospheric stability, excellent chemical stability, strong fire resistance, convenient construction and comprehensive protection performance. These advantages make perchloroethylene paint widely used in many fields. Perchloroethylene paint has the characteristic of retaining solvents, which means that although the surface of the paint film dries quickly, it dries slowly completely. Before the retained solvent evaporates, the paint film will become soft and have poor adhesion. The film-forming substances of perchloroethylene paint have a kind of occlusion of solvents, which further slows down the evaporation rate of solvents. Compared with film-forming substances with good release properties, it is more difficult to evaporate solvents from peroxide ethylene paint.
[0003] The perchlorethylene paint traditionally used for heat shields dries slowly and takes more than a week to cure. The non-drying nature of the paint on the heat shield surface directly affects the service life and safety of the product. Non-drying paint not only leads to poor appearance, but also causes problems such as coating peeling and performance degradation.
[0004] Therefore need to develop a kind of preparation process of quick-drying perchloroethylene paint layer. Summary of the invention
[0005] The object of the present invention is to provide a preparation process of a quick-drying perchloroethylene paint layer, by which the time for the perchloroethylene paint layer to be completely dried can be greatly reduced, and the prepared quick-drying perchloroethylene paint layer has good adhesion to a substrate and good durability.
[0006] The purpose of the present invention can be achieved through the following technical solutions: A preparation process of a quick-drying perchloroethylene paint layer comprises the following steps: S1. Preparation of perchloroethylene paint: In parts by weight, at 35-45° C., add 0.2-0.4 parts of dispersant, 1-2 parts of plasticizer, 10-15 parts of solvent and 7-10 parts of filler into a batching tank, stir at a speed of 300-500 r / min for 25-35 min, add 50-65 parts of perchloroethylene resin and 0.5-1.5 parts of leveling agent while maintaining the speed, and continue stirring for 1-3 hours to obtain perchloroethylene paint; S2. Preparation of perchloroethylene paint materials: The perchloroethylene paint and the diluent are mixed in a mass ratio of 1:3 to prepare a perchloroethylene paint preparation; S3, preparing perchlorethylene paint layer: The perchloroethylene preparation material is sprayed on a heat shield substrate through an ultrasonic spraying process and dried at room temperature for 2 to 3 days to obtain a perchloroethylene paint layer, wherein the parameters of the ultrasonic spraying are: a liquid feed rate of 10 to 50 mL / min, a working feed rate of 200 to 800 mm / min, and a power of an ultrasonic nozzle of 3 to 7 W.
[0007] As a preferred technical solution of the present invention, in step S1, the preparation process of the filler is as follows: The sodium sucrose octasulfate was mixed with pure water, and ultrasonically dispersed for 0.5 to 1 h at a frequency of 45 to 55 kHz to obtain a dispersion with a mass fraction of 10 to 15%, and the dispersion and nano-silicon dioxide were stirred at a speed of 300 to 500 r / min for 30 min, and then stirred for 1 to 2 h at a temperature of 75 to 85 ° C, and then placed in a vacuum drying oven and dried for 15 to 19 h at a temperature of 80 to 95 ° C to obtain pretreated nano-silicon dioxide; The pretreated nano-silica and chitosan dispersion with a mass of 5-10% of the pretreated nano-silica were ball-milled at a speed of 500-700 r / min for 1-3 hours. After the ball-milling, the mixture was washed with water and dried at 105°C for 8 hours to obtain modified nano-silica. Treating the expanded pearlite powder by low-temperature plasma technology for 1 to 2 hours, wherein the low-temperature plasma action voltage is 10 to 25 kV, and the low-temperature plasma action atmosphere is air mixed with 2 to 8% ammonia, to obtain pretreated expanded pearlite powder; The filler is obtained by ball-milling modified nano-silicon dioxide and pretreated expanded pearlite powder in a mass ratio of 1:1 and then passing through a 200-mesh sieve.
[0008] As a preferred technical solution of the present invention, in step S1, the dispersant is one of polyvinyl pyrrolidone and sodium polymethacrylate.
[0009] As a preferred technical solution of the present invention, in step S1, the plasticizer is triisooctyl phosphite.
[0010] As a preferred technical solution of the present invention, in step S1, the solvent is one or more of acetone, sec-butyl acetate and butyl acetate.
[0011] As a preferred technical solution of the present invention, in step S1, the leveling agent is one of BYK346, BYK348 and BYK370.
[0012] As a preferred technical solution of the present invention, in step S2, the diluent is perchloroethylene diluent.
[0013] As a preferred technical solution of the present invention, the chitosan dispersion is a chitosan solution with a mass fraction of 10-15%, and the solvent in the chitosan solution is an acetic acid solution with a volume concentration of 2-3%.
[0014] As a preferred technical solution of the present invention, the solid-liquid ratio of the nano-silicon dioxide to the dispersion liquid is 1-3:20 g / mL.
[0015] As a preferred technical solution of the present invention, the rotation speed of the ball mill during the ball milling is 500r / min and the time is 3h.
[0016] Sodium sucrose octasulfate is a negatively charged compound. The sulfate groups in its molecules can interact with the hydroxyl groups on the surface of nano-silica, thereby making the surface of nano-silica negatively charged. This charge change helps to disperse and stabilize the nano-silica when it is mixed with subsequent chitosan, preventing it from agglomerating and precipitating, thereby optimizing the adhesion of the system.
[0017] In the present invention, chitosan dispersion is used as a ball milling agent to modify the pretreated nano silicon dioxide. The surface of the pretreated nano silicon dioxide is wetted by the chitosan dispersion. Chitosan is a natural polymer compound with good biocompatibility and degradability, while nano silicon dioxide has characteristics such as small size effect and surface interface effect. Chitosan and the pretreated nano silicon dioxide are subjected to ball milling and mixed treatment. As an organic polymer, the flexibility of the molecular chain and the diversity of the functional groups of chitosan make it easier to be compatible with the perchlorethylene paint matrix material, thereby enhancing the compatibility between nano silicon dioxide and the organic matrix. In addition, chitosan can reduce its surface energy by adsorption or coating on the surface of nano silicon dioxide, thereby improving dispersibility and stability.
[0018] The expanded perlite powder is surface treated by plasma to increase the active points and polar groups on its surface, improve the interaction between the expanded perlite powder and the paint, and thus enhance the compatibility and adhesion.
[0019] The filler is prepared by mixing modified nano-silica with pre-treated expanded perlite powder by ball milling. The expanded perlite powder itself has many closed microporous structures, which can effectively reduce the convection of gas, thus giving it excellent thermal insulation performance. Since the expanded perlite has a porous structure, there are a large number of adsorption sites on its surface. And the nano-silica particles are modified, so they can be attached to the surface of the pre-treated expanded perlite powder with increased active sites through physical adsorption, which helps to enhance the interface compatibility, improve the overall stability and dispersibility of the filler, and thus help to improve the adhesion of the paint.
[0020] After the filler is mixed with perchloroethylene, the filler's tiny particle size and large specific surface area enable it to adhere tightly to the surface of the coating substrate, thereby improving the adhesion of the coating; and the filler surface can further enhance the interface interaction between the filler and the perchloroethylene coating substrate through intermolecular forces with the chlorine atoms in the perchloroethylene molecules, thereby improving the adhesion and overall performance of the coating. This interaction can further enhance the bonding force between the coating and the substrate, allowing the coating to adhere more firmly to the surface of the heat shield substrate, thereby improving the durability of the paint layer.
[0021] Expanded perlite has a porous structure and a low bulk density, which is beneficial to improving the adsorption performance of the coating, promoting the volatilization of the solvent in the paint, making the surface drying and actual drying of the coating consistent, and helping to increase the drying rate of the perchlorethylene coating.
[0022] Before spraying perchloroethylene paint, add diluent to mix it. By increasing the solvent content in the perchloroethylene paint to reduce the solute concentration, the solvent in the paint layer can be evaporated and dried quickly, making the paint layer hard in a short time.
[0023] Beneficial effects of the present invention: The invention prepares a quick-drying perchloroethylene paint layer, wherein the compatibility and interface interaction between the filler and the coating are improved by using a filler obtained by mixing modified nano-silicon dioxide and expanded perlite, thereby enhancing the bonding force between the paint layer and the heat shield substrate, improving the durability of the paint layer, and solving the problem that the traditional perchloroethylene paint layer is difficult to quickly and completely dry in a short time by mixing with a diluent. DETAILED DESCRIPTION
[0024] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0025] In the comparative examples and embodiments of the present invention: Perchloroethylene diluent: Eye brand, brand number X-3; Perchlorethylene resin: purchased from Hubei Chengfeng Chemical Co., Ltd. Nano-silicon dioxide: purchased from Hubei Fangde New Materials Co., Ltd.; Chitosan: purchased from Shanghai Yien Chemical Technology Co., Ltd.; Sucrose octasulfate sodium: purchased from Hubei Yongkuo Technology Co., Ltd., product number: YK0279; Polyvinyl pyrrolidone: purchased from Hefei Hongrui Biotechnology Co., Ltd.; Tri(2-ethylhexyl) phosphite: purchased from Hubei Xinhongli Chemical Co., Ltd., product number: XHL6300.
[0026] BYK346: purchased from Dongguan Ruikun Material Technology Co., Ltd.
[0027] Example 1 S1. Preparation of perchloroethylene paint: Preparation of filler: The sodium sucrose octasulfate was mixed with pure water, and ultrasonically dispersed for 0.5 h at a frequency of 45 kHz to obtain a dispersion with a mass fraction of 10%. The dispersion and nano-silicon dioxide were stirred at a speed of 300 r / min for 30 min, and then stirred for 1 h at a temperature of 75 ° C. The mixture was placed in a vacuum drying oven and dried at a temperature of 80 ° C for 15 h to obtain pretreated nano-silicon dioxide, wherein the solid-liquid ratio of nano-silicon dioxide to the dispersion was 1:20 g / mL; The pretreated nano-silica was mixed with a chitosan dispersion liquid with a mass fraction of 5% of the pretreated nano-silica, and the mixture was ball-milled at a speed of 500 r / min for 1 h. After the ball-milling, the mixture was washed with water and dried at 105° C. for 8 h to obtain modified nano-silica, wherein the chitosan dispersion liquid was a chitosan solution with a mass fraction of 10%, and the solvent in the chitosan solution was an acetic acid solution with a volume concentration of 2%; The expanded pearlite powder was treated by low-temperature plasma technology for 1 hour, wherein the low-temperature plasma action voltage was 10 kV, and the low-temperature plasma action atmosphere was air mixed with 2% ammonia, to obtain pretreated expanded pearlite powder; The modified nano-silicon dioxide and pre-treated expanded pearlite powder in a mass ratio of 1:1 are ball-milled at a speed of 500 r / min for 3 hours and then passed through a 200-mesh sieve to obtain the filler; In parts by weight, at 35°C, 0.2 parts of polyvinyl pyrrolidone, 1 part of triisooctyl phosphite, 10 parts of acetone and 7 parts of filler are added to a mixing tank, stirred at a speed of 300 r / min for 25 minutes, and 50 parts of perchloroethylene resin and 0.5 parts of BYK346 are added while maintaining the speed and stirring is continued for 1 hour to obtain perchloroethylene paint; S2. Preparation of perchloroethylene paint materials: The perchloroethylene paint and the perchloroethylene diluent are mixed in a mass ratio of 1:3 to prepare a perchloroethylene paint preparation; S3, preparing perchlorethylene paint layer: The perchloroethylene preparation material is sprayed on the heat shield substrate through an ultrasonic spraying process and dried at room temperature for 2 days to obtain a perchloroethylene paint layer, wherein the parameters of the ultrasonic spraying are: a liquid feed rate of 10 mL / min, a working feed rate of 200 mm / min, and a power of the ultrasonic nozzle of 3 W.
[0028] Example 2 S1. Preparation of perchloroethylene paint: Preparation of filler: The sodium sucrose octasulfate was mixed with pure water, and ultrasonically dispersed for 0.8 h at a frequency of 50 kHz to obtain a dispersion with a mass fraction of 12%. The dispersion and nano-silicon dioxide were stirred at a speed of 400 r / min for 30 min, and then stirred for 1.5 h at a temperature of 80 ° C. The mixture was placed in a vacuum drying oven and dried at a temperature of 87 ° C for 17 h to obtain pretreated nano-silicon dioxide, wherein the solid-liquid ratio of nano-silicon dioxide to the dispersion was 2:20 g / mL; The pretreated nano-silica was mixed with a chitosan dispersion liquid with a mass fraction of 7% of the pretreated nano-silica, and the mixture was ball-milled at a speed of 600 r / min for 2 h. After the ball-milling, the mixture was washed with water and dried at 105°C for 8 h to obtain the modified nano-silica. The chitosan dispersion liquid was a chitosan solution with a mass fraction of 13%, and the solvent in the chitosan solution was an acetic acid solution with a volume concentration of 2.5%. The expanded pearlite powder was treated by low-temperature plasma technology for 1.5 hours, wherein the low-temperature plasma action voltage was 18 kV, and the low-temperature plasma action atmosphere was air mixed with 5% ammonia, to obtain pretreated expanded pearlite powder; The modified nano-silicon dioxide and pre-treated expanded pearlite in a mass ratio of 1:1 are ball-milled at a speed of 500 r / min for 3 hours and then passed through a 200-mesh sieve to obtain the filler; In parts by weight, at 40° C., 0.3 parts of polyvinyl pyrrolidone, 1.5 parts of triisooctyl phosphite, 13 parts of acetone and 8 parts of filler are added to a mixing tank, stirred at a speed of 400 r / min for 30 minutes, and 57 parts of perchloroethylene resin and 1 part of BYK346 are added while maintaining the speed and stirring is continued for 2 hours to obtain a perchloroethylene paint; S2. Preparation of perchloroethylene paint materials: The perchloroethylene paint and the perchloroethylene diluent are mixed in a mass ratio of 1:3 to prepare a perchloroethylene paint preparation; S3, preparing perchlorethylene paint layer: The perchloroethylene preparation material is sprayed on the heat shield substrate through an ultrasonic spraying process and dried at room temperature for 2 days to obtain a perchloroethylene paint layer, wherein the parameters of the ultrasonic spraying are: a liquid feed rate of 20 mL / min, a working feed rate of 500 mm / min, and a power of the ultrasonic nozzle of 4 W.
[0029] Example 3 S1. Preparation of perchloroethylene paint: Preparation of filler: The sodium sucrose octasulfate was mixed with pure water, and ultrasonically dispersed for 1 hour at a frequency of 55kHz to obtain a dispersion with a mass fraction of 15%. The dispersion and nano-silicon dioxide were stirred at a speed of 500r / min for 30 minutes, and then stirred for 2 hours at a temperature of 85°C, and then placed in a vacuum drying oven and dried at a temperature of 95°C for 19 hours to obtain pretreated nano-silicon dioxide, wherein the solid-liquid ratio of nano-silicon dioxide to the dispersion was 3:20g / mL; The pretreated nano-silica and chitosan dispersion with a mass fraction of 10% of the pretreated nano-silica were ball-milled at a speed of 700 r / min for 3 hours. After the ball-milling, the mixture was washed with water and dried at 105°C for 8 hours to obtain modified nano-silica. The chitosan dispersion was a chitosan solution with a mass fraction of 15%, and the solvent in the chitosan solution was an acetic acid solution with a volume concentration of 3%. The expanded pearlite powder was treated by low-temperature plasma technology for 2 hours, wherein the low-temperature plasma action voltage was 25 kV, and the low-temperature plasma action atmosphere was air mixed with 8% ammonia, to obtain pretreated expanded pearlite powder; The modified nano-silicon dioxide and pre-treated expanded pearlite in a mass ratio of 1:1 are ball-milled at a speed of 500 r / min for 3 hours and then passed through a 200-mesh sieve to obtain the filler; In parts by weight, at 45°C, 0.4 parts of polyvinyl pyrrolidone, 2 parts of triisooctyl phosphite, 15 parts of acetone and 10 parts of filler are added to a mixing tank, stirred at a speed of 500 r / min for 35 minutes, and 65 parts of perchloroethylene resin and 1.5 parts of BYK346 are added while maintaining the speed and stirring is continued for 3 hours to obtain a perchloroethylene paint; S2. Preparation of perchloroethylene paint materials: The perchloroethylene paint and the perchloroethylene diluent are mixed in a mass ratio of 1:3 to prepare a perchloroethylene paint preparation; S3, preparing perchlorethylene paint layer: The perchloroethylene preparation material is sprayed on the heat shield substrate through an ultrasonic spraying process and dried at room temperature for 3 days to obtain a perchloroethylene paint layer, wherein the parameters of the ultrasonic spraying are: a liquid feed rate of 50 mL / min, a working feed rate of 800 mm / min, and a power of the ultrasonic nozzle of 7 W.
[0030] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that the nano-silicon dioxide in Comparative Example 1 is not subjected to any modification treatment, and the other operations are the same.
[0031] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that no nano-silicon dioxide is added in Comparative Example 2, and the other operations are the same.
[0032] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that no diluent is added when preparing the perchloroethylene paint layer in Comparative Example 3, and the other operations are the same.
[0033] Performance Testing: 1. Adhesion test: Adhesion was tested according to GB / T5210-2006 coating adhesion test method (pull-off method). The results are shown in Table 1: Table 1
[0034] 2. Drying time: Tested according to GB / T1728-1979 standard, the results are shown in Table 2: Table 2
[0035] According to the above data, the perchloroethylene paint layer prepared by the present invention has a fast drying speed and strong adhesion.
[0036] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A process for preparing a quick-drying perchloroethylene paint layer, characterized in that: The following steps are involved: S1. Preparation of perchloroethylene paint: In parts by weight, at 35-45° C., add 0.2-0.4 parts of dispersant, 1-2 parts of plasticizer, 10-15 parts of solvent and 7-10 parts of filler into a batching tank, stir at a speed of 300-500 r / min for 25-35 min, add 50-65 parts of perchloroethylene resin and 0.5-1.5 parts of leveling agent while maintaining the speed, and continue stirring for 1-3 hours to obtain perchloroethylene paint; S2. Preparation of perchloroethylene paint materials: The perchloroethylene paint and the diluent are mixed in a mass ratio of 1:3 to prepare a perchloroethylene paint preparation; S3, preparing perchlorethylene paint layer: The perchloroethylene preparation material is sprayed on a heat shield substrate through an ultrasonic spraying process and dried at room temperature for 2 to 3 days to obtain a perchloroethylene paint layer, wherein the parameters of the ultrasonic spraying are: a liquid feed rate of 10 to 50 mL / min, a working feed rate of 200 to 800 mm / min, and a power of an ultrasonic nozzle of 3 to 7 W.
2. The process for preparing the quick-drying perchloroethylene paint layer according to claim 1, characterized in that: In step S1, the preparation process of the filler is as follows: The sodium sucrose octasulfate was mixed with pure water, and ultrasonically dispersed for 0.5 to 1 h at a frequency of 45 to 55 kHz to obtain a dispersion with a mass fraction of 10 to 15%, and the dispersion and nano-silicon dioxide were stirred at a speed of 300 to 500 r / min for 30 min, and then stirred for 1 to 2 h at a temperature of 75 to 85 ° C, and then placed in a vacuum drying oven and dried for 15 to 19 h at a temperature of 80 to 95 ° C to obtain pretreated nano-silicon dioxide; The pretreated nano-silica and chitosan dispersion with a mass of 5-10% of the pretreated nano-silica were ball-milled at a speed of 500-700 r / min for 1-3 hours. After the ball-milling, the mixture was washed with water and dried at 105°C for 8 hours to obtain modified nano-silica. Treating the expanded pearlite powder by low-temperature plasma technology for 1 to 2 hours, wherein the low-temperature plasma action voltage is 10 to 25 kV, and the low-temperature plasma action atmosphere is air mixed with 2 to 8% ammonia, to obtain pretreated expanded pearlite powder; The filler is obtained by ball-milling modified nano-silicon dioxide and pretreated expanded pearlite powder in a mass ratio of 1:1 and then passing through a 200-mesh sieve.
3. The process for preparing the quick-drying perchloroethylene paint layer according to claim 1, characterized in that: In step S1, the dispersant is one of polyvinyl pyrrolidone and sodium polymethacrylate.
4. The process for preparing the quick-drying perchloroethylene paint layer according to claim 1, characterized in that: In step S1, the plasticizer is triisooctyl phosphite.
5. The process for preparing the quick-drying perchloroethylene paint layer according to claim 1, characterized in that: In step S1, the solvent is one or more of acetone, sec-butyl acetate and butyl acetate.
6. The process for preparing the quick-drying perchloroethylene paint layer according to claim 1, characterized in that: In step S1, the leveling agent is one of BYK346, BYK348 and BYK370.
7. The process for preparing the quick-drying perchloroethylene paint layer according to claim 1, characterized in that: In step S2, the diluent is perchloroethylene diluent.
8. The process for preparing the quick-drying perchloroethylene paint layer according to claim 2, characterized in that: The chitosan dispersion is a chitosan solution with a mass fraction of 10-15%, and the solvent in the chitosan solution is an acetic acid solution with a volume concentration of 2-3%.
9. The process for preparing the quick-drying perchloroethylene paint layer according to claim 2, characterized in that: The solid-liquid ratio of the nano-silicon dioxide to the dispersion liquid is 1-3:20 g / mL.
10. The process for preparing the quick-drying perchloroethylene paint layer according to claim 2, characterized in that: The ball mill has a rotation speed of 500 r / min and a time of 3 h during the ball milling.
Citation Information
Patent Citations
Steel structure fireproof coating and preparation method thereof
CN105542587A
Method for preparing vinyl-perchloride fireproof coating by adopting amine-loaded perlite as flame-retarding agent
CN108342133A
Expanding type modification perchloroethene refractory paint
CN1084868A
Non-benzenoid universal diluent
CN1105687A